MANAGEMENT OF LOW VISION IN PEOPLE WITH MYOPIC MACULAR DEGENERATION - Shah, Mufarriq; Khan, Muhammad Tariq (Journal of Postgraduate Medical Institute, 2021)
Objective: To assess the effectiveness of correction of refractive error, use of contact lenses and low vision aids in visual rehabilitation of people with Myopic Macular Degeneration (MMD). Methodology: This cross-sectional study included participants with MMD assessed for visual rehabilitation in a low vision clinic at Department of Ophthalmology Hayatabad Medical Complex, Peshawar, from June 2017 to June 2020. Data regarding distance and near visual acuities at the time of presentation with amount of myopia, best corrected visual acuity (VA) with glasses and contact lenses, VA with low vision devices and types of low vision devices prescribed were collected and analyzed. VA was recorded on Logarithm of the Minimum Angle of Resolution (LogMAR) chart. Data was analyzed using SPSS v.19.0. Results: Out of 78 participants with MMD, 74.4% were male with mean age was 29.13±19.1 years. About 22% had vision impairment with their own glasses, 19% had severe impairment and 59% had blindness. Mean spherical equivalent refractive error amongst participants was -14.56 ± 5.39D and -12.52 ± 6.64D in right and left eyes respectively. With optimum correction (glasses/contact lenses) in 41% of participants distance VA was improved to 6/18 (0.54 Log MAR) or better in the better-seeing eye. With low vision devices, mean distance visual acuity was enhanced to 0.18 Log MAR (p<0.001). Conclusion: Correction of myopia is very important in visual rehabilitation of people with MMD. Low vision aids can be successfully used to enhance the residual vision among people with MMD in order to improve life efficiency.